ON THE FUTURE OF TEACHING PREACHING IN THE MIDST OF THE COVID-19 PANDEMIC - J.E. Alcantara (Acta Theologica)
In this article, I commend a way forward in preaching pedagogy over the next ten years. I propose a turn toward improvisational teaching that is technologically innovative, intentionally collaborative, and strategically diverse. These commitments arise from ongoing pedagogical research, teaching and learning experiences in classrooms and conferences, dialogues with colleagues, and most importantly, from listening to students at various seminaries and divinity schools discuss how they learn, grow, and thrive as preachers.